MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN MELALUI PENERAPAN KOOPERATIF MODEL NUMBERED HEADS TOGETHER PADA SISWA KELAS VI SDN 01 BARADATUKABUPATEN WAY KANAN TP. 2019/2020 - Muhamad Muhamad (STAI Al-Ma`arif Way Kanan Lampung, 2020)
This research is a Classroom Action Research conducted in 2 cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of the study were Grade VI students of Baradatu State Elementary School 01 2019/2020. Before using the Numbered Heads Together Model Learning Method in learning Citizenship Education for Class VI students of State Elementary Schools 01 Baradatu Learning Activity Classically students in participating in learning is 48.13% and after using the Numbered Heads Together Model Learning Method classically the students' affective value in participating in learning is 85.13% so it achieves an increase in the affective value classically by 37.00%. Before using the Numbered Heads Together Model Learning Method in learning Citizenship Education for Class VI students of State Elementary School 01 Baradatu. Student Learning Outcomes classically in participating in learning is 38.46% and after using the Numbered Heads Together Model Learning Method in the classically affective value of students in following learning is 92.31% so it achieves an increase in the classical psychomotor value of 53.85%. Before using the Numbered Heads Together Model Learning Method in learning Citizenship Education for Class VI students of Primary Schools 01 Baradatunilai The portfolio of students 'classical documents in participating in learning is 49.67% and after using the Numbered Heads Together Model Learning Method in classically affective students' grades in participating in learning is 86.67% so achieving a classical psychomotor value increase of 37.00%. The application of the Learning Method Model Numbered Heads Together has a positive effect, which can increase student learning motivation as indicated by the results of interviews with some students, the average student answers state that students are interested and interested in demonstration learning methods so that they become motivated to learn.